2021
DOI: 10.15366/rimcafd2021.81.005
|View full text |Cite
|
Sign up to set email alerts
|

Aula Invertida en Educación Física: Aprendizaje, Motivación Y Tiempo De Práctica Motriz

Abstract: La metodología Flipped Learning (FL) está emergiendo como un enfoque pedagógico innovador que enriquece el proceso de enseñanza-aprendizaje mediante el uso de las TIC. Este estudio pretende evaluar los efectos de su aplicación práctica en las clases de EF de ESO. Para ello, se desarrolló la misma Unidad didáctica sobre Pelota Valenciana en 7 grupos de 1º ESO, aplicando dos metodologías diferentes: FL (FLIP) o tradicional (TRAD). Se evaluaron los niveles de aprendizaje, motivación y tiempo de práctica motriz pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
7

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
1
4
0
7
Order By: Relevance
“…On the other hand, and somewhat opposing the findings in the present study, scholars like Chiang et al (2018) found girls to take better advantage of the FL approach, as they were more likely to use the opportunity to see instructional videos, online, outside school hours. Finally, one must interpret the findings in the present study with findings that both diverge and converge in their conclusions, such as the results from Ferriz-Valero et al (2017), Campos-Gutiérrez et al (2021), and Gómez-García et al (2019, who found FL not to affect student motivation and/or learning in PE. This variety in findings might be caused by the reality that FL in PE is still in its very infancy, both in practice and in research, and that most studies still evolve around fragmented parts of the subject PE, and for shorter time of periods.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…On the other hand, and somewhat opposing the findings in the present study, scholars like Chiang et al (2018) found girls to take better advantage of the FL approach, as they were more likely to use the opportunity to see instructional videos, online, outside school hours. Finally, one must interpret the findings in the present study with findings that both diverge and converge in their conclusions, such as the results from Ferriz-Valero et al (2017), Campos-Gutiérrez et al (2021), and Gómez-García et al (2019, who found FL not to affect student motivation and/or learning in PE. This variety in findings might be caused by the reality that FL in PE is still in its very infancy, both in practice and in research, and that most studies still evolve around fragmented parts of the subject PE, and for shorter time of periods.…”
Section: Discussionsupporting
confidence: 55%
“…The present investigation is based on a natural experiment with a non-randomized controlled design with a pre-and a post-measure (Verjans-Janssen et al, 2018). The design reflected the layouts in similar studies (Botella et al, 2021;Campos-Gutiérrez et al, 2021;Cuenca-Ruano et al, 2021;Østerlie and Mehus, 2020). The study was approved by the University of Alicante´s Research Ethics Committee on 2 September 2020, and given the code UA-2020-09-02.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Al respecto, los contenidos teóricos desarrollados a través de clases magistrales por los docentes durante la sesión cambian y serán estudiados previamente por el estudiantado. Este proceso mediado por TIC en un entorno virtual de aprendizaje permite que el tiempo sincrónico de la sesión sea utilizado para evacuar dudas, generar actividades de mediación activa, con el propósito de aplicar los conocimientos teóricos previos y consolidar el aprendizaje de forma participativa y colaborativa en el grupo de estudiantes (Campos-Gutiérrez et al, 2021;Kuzminska et al, 2017).…”
Section: Reflexiones Y Experiencias Investigativas Para La Innovaciónunclassified